Biological characterization and in vitro fungicide screening of a new causal agent of walnut leaf spot in Guizhou Province, China - Ao, Xianxi; Shi, Ting; Yang, Wenjia; Ouyang, Hao; Fan, Ruidong; Siddiqui, Junaid Ali; Wu, Chaoming; Lv, Zhoule; Deng, Shasha; Chen, Xiaoyulong (Frontiers in Microbiology, 2024)
Walnut (Juglans regia L.) is a widely grown nut plant worldwide, including in Guizhou Province, located in southwest China. The high quality and special taste make Guizhou walnuts, particularly those produced in Hezhang County, a "Chinese National Geographical Indication Product" that substantially contributes to the local economy and grower's income. In July 2022, a serious occurrence of leaf spot disease was observed in a walnut plantation area, Shuitang Town, Hezhang County, Guizhou Province, China (27°07′67″N, 104°64′61″E). The causal agent was identified as Didymella segeticola through morphological characterization and amplification and sequencing of the internal transcribed spacer (ITS) region, beta-tubulin (TUB) gene, and glyceraldehyde-3phosphate dehydrogenase (G3PD) gene. Koch's postulates, including re-isolation and identification, were performed to confirm its pathogenicity on healthy leaves. To our knowledge, this is the first report of D. segeticola causing leaf spot on walnuts worldwide. Further, to determine its biological characteristics, which could be utilized for future disease management, the effects of temperature, light, and carbon and nitrogen resources on mycelial growth, conidia production, and conidia germination and the effects of humidity on conidia germination were studied. The optimum temperature for mycelial growth of representative strain D. segeticola C27 was 20°C. Increasing the light period significantly decreased conidia production and conidia germination. Maltose and beef extract were the best carbon and nitrogen sources, respectively, for the pathogen. Conidia germination was enhanced at 90% humidity. In vitro screening of effective fungicides was conducted.Among the 20 screened fungicides, difenoconazole showed the best inhibition rate, with an EC50 (concentration for 50% of the maximal effect) of 0.0007 μg/mL. Tetramycin also showed sufficient 2 inhibitory effects against D. segeticola, with an EC50 value of 0.0009 μg/mL. Our study provides new insights into the causal agent of walnut leaf spot in Guizhou, China, as well as the first pathogen characteristics and promising candidate fungicides for its management.